2011
DOI: 10.1007/s11164-011-0247-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution rates of silicate minerals in water from a subcritical to a supercritical state: effect of solvent properties

Abstract: Hydrothermal reaction experiments of silicate minerals (actinolite, pyroxene, etc.) were carried out using flow-through reactors in the temperature range from 25 to 400°C at 23 MPa. The dissolution in water of a multi-oxide silicate mineral, for example actinolite or pyroxene may require the breaking of more than one type of metal-oxygen bond. Differences between the rates at which these bonds break are often sufficiently large for dissolution to be non-stoichiometric. Dissolution rates (of Si) for actinolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Under high pressures and high temperatures in aqueous solution, the solubility of silicon and aluminium such as hydrated silica Si(OH)4 and aluminium hydroxide Al(OH)3 were dramatically increased. Thus, the metakaolin was persistently solved to release silicate and aluminium which were dispersed in the water as precursors (Cassiers et al, 2002;Zhang et al, 2011). On the other hand, a part of solute agglomerated and precipitated into solid cores, so that sphere particulates in size of about 100 nm were seen in the SEM and TEM images.…”
Section: The Formation Mechanism Of the Synthetic Silicatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under high pressures and high temperatures in aqueous solution, the solubility of silicon and aluminium such as hydrated silica Si(OH)4 and aluminium hydroxide Al(OH)3 were dramatically increased. Thus, the metakaolin was persistently solved to release silicate and aluminium which were dispersed in the water as precursors (Cassiers et al, 2002;Zhang et al, 2011). On the other hand, a part of solute agglomerated and precipitated into solid cores, so that sphere particulates in size of about 100 nm were seen in the SEM and TEM images.…”
Section: The Formation Mechanism Of the Synthetic Silicatesmentioning
confidence: 99%
“…Hydrothermal treatment is widely used for the synthesis of zeolite from aluminosilicate including kaolin, and the product generated can be altered by varying the operating parameters and additives used in the production (Krol et al, 2018;Wu et al, 2013). Pressurised hydrothermal treatment can generate different minerals and accelerate the synthesis process (Zhang et al, 2011;Hayashi et al, 2010), and has proved to create larger surface area silicates (Sun et al, 2008). However, only a two studies in the literature have reported modifying kaolin by hydrothermal methods and most focused on the dihydrogen during the hydrothermal treatment, but neither studied its aluminosilicate structure nor have been further used as a high temperature sorbent (Zemenová et al, 2014;Kloužková et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The values of the activation energy E a and K o are obtained from a linear relationship between -lnK r and 1/T. The activation energy for a product layer diffusion-controlled reaction is usually below 20 kJ mol -1 and for a chemically controlled reaction 40-80 kJ mol -1 [18,19]. Therefore, a precise evaluation of the activation energy is needed in order to determine the reaction mechanism.…”
Section: Shrinking Core Model Theorymentioning
confidence: 99%